The Analysis of Physical Education Learning and Environment of Character Education-Based School. (March 2017) - Mulyana,; Suherman, A
Abstract: The research reveals a link between the implementation model of character education through the physical education learning facilities and infrastructures. The study involved 20 schools in the city of Bandung to analyse the extent of support facilities within the school environment in the character education-oriented physical education learning process. Instruments on the "physical education process and products is based on the perceptions of students." Instruments of physical education learning facilities include sports fields, land areas, sports equipment and more. Based on the analysis, it's found that the apparent correlation coefficient between the infrastructures and learning effectiveness is 0.396 with a probability of 0.000 <0.05, thus the direction of the relationship between these two variables is in line with the low level of correlation, and analysis hypothesis is accepted, which means there is a significant relationship between infrastructures and the effectiveness of learning. In detail, it can be described that the correlation coefficient between the factors of external support, the students' behaviours, and skills, and learning effectiveness of each student is 0.504 ( P = 0.000), 0.439 ( P = 0.000) and 0.533 ( P = 0.000), therefore, the direction of the relationship between each aforementioned variable and learning effectiveness is unidirectional, and each probability's value is <0.05 and analytical hypothesis is accepted, which means that there is a relationship between the factors of external support, students' behaviours and skills, and learning effectiveness.